Gramazio Kohler Research, Automated Diversity: New Morphologies of Vertical Urbanism. (November 2015) - Willmann, Jan; Gramazio, Fabio; Kohler, Matthias
Abstract : Automated fabrication techniques are currently largely confined to the production of discrete objects or building elements. To notch up the potential of robotics for architectural design, it is necessary to start to push the limits and experiment at a larger urban scale.Fabio Gramazio and Matthias Kohler are pioneers in this field. Here, withJan Willmann, they describe the research that they are undertaking as part of the Future Cities Laboratory (FCL) located at the Singapore‐ETH Centre for Global Environmental Sustainability (SEC) and ETH Zurich, in which robotic fabrication technologies are employed to realize 1:50 physical models of mixed‐use high‐rise structures that are unique in their spatial layouts.